Membangun Keterampilan Berbahasa Terstruktur dan Produktif yang Membangun Pikiran dalam Pembelajaran - Khairul Huda (Balai Diklat Keagamaan Semarang, 2022)
In general, language skills developed in the world of education have not been able to increase learning productivity and build students' minds. The purpose of writing this article is to see how to build well-structured speaking skills and how to use language or discussion productively in learning. The writing of this article uses a qualitative descriptive approach. The type of research used is library research or (Library Research), namely by collecting library data relevant to this article. The primary source for writing this article is David D. Preiss and Robert J. Sternberg's book entitled